Tracing China : A Forty-Year Ethnographic Journey - Siu, Helen F. (Book collections on Project MUSE., 2016)
Tracing China chronicles forty years of fieldwork. The journey began from exploring rural revolution and reconstitutions of community in South China; it spans decades of persistent rural-urban divide and eventually uncovers China's global reach and Hong Kong's cross-border dynamics. Siu traverses both physical and cultural landscapes, examines how political tumults transform into everyday lives, and fathoms the depths of human drama amid China's frenetic momentum toward modernity. She highlights complicity, portraying how villagers, urbanites, cadres, entrepreneurs, and intellectuals--laden with historical baggage--venture forward. The question is: Have they become victims of the circumstances created by their own actions? The essays are woven together by key themes in historical anthropology--culture, history, power, place-making, and identity formation, informed by critical social theories, and characterized by a careful scrutiny of fieldwork encounters and archival texts. Stressing process and contingency, Siu argues that culture and society are constructed through human actions with nuanced meanings, moral imagination, and contested interests. She challenges the perception that social/political changes are merely linear historical progressions. Instead, she traces layers of the past in present realities.